A FATAL FLAW: DOMESTIC BANKS AND MEXICO'S INTERNATIONAL NEGOTIATING POSITION IN THE 1982 DEBT CRISIS. (30th August 2018) - Alvarez, Sebastian
Abstract: The recent European debt crisis has renewed interest as to why debtor countries honour their foreign debts and subscribe to respectively burdensome rescheduling conditions. While the cost of defaulting in a domestic financial system has been recognised as a main motive for repayment, the factors that cause sovereign states to refrain from debt repudiation are not fully understood. This article investigates the reasons behind the repayment decision and weak negotiating position of the Mexican government following the 1982 debt crisis. It shows that leading commercial banks had considerable amounts of external loans in their books, and that Mexican policymakers lacked the foreign exchange access they needed to secure the stability of the domestic banking system. The high exposure of domestic banks to Mexican debt and their heightened dependence on foreign capital worked as mechanisms that allowed international creditors to enforce their claims and deterred Mexico from declaring a unilateral default. RESUMEN: La reciente crisis de la deuda europea ha renovado el interés en por qué los países deudores pagan su deuda externa y aceptan pesadas condiciones de renegociación. Si bien los costos de un default para el sistema financiero doméstico han sido reconocidos como un motivo primordial de repago, los factores por los que disuade a los gobiernos de repudiar la deuda no se comprenden plenamente todavía. Este artículo investiga las razones detrás de la decisión de pago y la débil posición negociadora del gobierno mexicano en los albores de la crisis de la deuda de 1982. El artículo muestra que los bancos comerciales líderes tenían considerables montos de deuda externa mexicana en sus libros y que las autoridades mexicanas no disponían de las divisas necesarias para asegurar la estabilidad del sistema bancario doméstico. La exposición de la banca doméstica a la deuda mexicana y su alta dependencia del capital extranjero funcionaron como un mecanismo que le permitió a los acreedores internacionales hacer respetar sus demandas y desalentó a México de declarar un default unilateral.